Usulan Business Continuity Plan untuk Memitigasi Risiko Supply Chain di PT. X - Karim, Daniel (Jurnal Administrasi Bisnis, 2015)
PT X is a smartphone retail company that distributing and selling smartphone from China and Hongkong to Indonesia. The length of their supply chain has a big potential risk on getting crushed by incidents that can stop their business process. The potential risk that will affect PT X is the risk of goods lost and broken as distributed from China and Hongkong. The separated distribution method, use of expeditions, and unpredictable weather could endangered those smartphone. Business Continuity Plan proposal for PT X focused on their ability to mitigate risks and incidents that might occur in their supply chain. Based on analysis, there are three options that PT X can apply, its (1) suppliers backup, (2) critical resources arrangement method, and (3) financial management systems. As the condition of PT X at the moment, suppliers back up and critical arrangement method assessed as their top implementable priority. Supported by AHP calculation, the two options chosen by PT X are the best options. Based on accumulation of those three options, option 1, Suppliers Back Up (43%) becomes their first priority with option 2 (35%) option 3 (22%) on their next list. Keywords: Business Continuity Plan, AHP, Risk Mitigation